The Central Circadian Clock Protein TaCCA1 Regulates Seedling Growth and Spike Development in Wheat (Triticum aestivum L.) - Gong, Jie; Tang, Yimiao; Liu, Yongjie; Sun, Renwei; Li, Yanhong; Ma, Jinxiu; Zhang, Shengquan; Zhang, Fengting; Chen, Zhaobo; Liao, Xiangzheng; Sun, Hui; Lu, Zefu; et al. (Frontiers in Plant Science, 2022)
The biological functions of the circadian clock on growth and development have been well elucidated in model plants, while its regulatory roles in crop species, especially the roles on yield-related traits, are poorly understood. In this study, we characterized the core clock gene CIRCADIAN CLOCK-ASSOCIATED 1 (CCA1) homoeologs in wheat and studied their biological functions in seedling growth and spike development. TaCCA1 homoeologs exhibit typical diurnal expression patterns, which are positively regulated by rhythmic histone modifications including histone H3 lysine 4 trimethylation (H3K4me3), histone H3 lysine 9 acetylation (H3K9Ac), and histone H3 lysine 36 trimethylation (H3K36me3). TaCCA1s are preferentially located in the nucleus and tend to form both homo- and heterodimers. TaCCA1 overexpression (TaCCA1-OE) transgenic wheat plants show disrupted circadian rhythmicity coupling with reduced chlorophyll and starch content, as well as biomass at seedling stage, also decreased spike length, grain number per spike, and grain size at the ripening stage. Further studies using DNA affinity purification followed by deep sequencing [DNA affinity purification and sequencing (DAP-seq)] indicated that TaCCA1 preferentially binds to sequences similarly to “evening elements” (EE) motif in the wheat genome, particularly genes associated with photosynthesis, carbon utilization, and auxin homeostasis, and decreased transcriptional levels of these target genes are observed in TaCCA1-OE transgenic wheat plants. Collectively, our study provides novel insights into a circadian-mediated mechanism of gene regulation to coordinate photosynthetic and metabolic activities in wheat, which is important for optimal plant growth and crop yield formation.